From Financial Literacy to Fintech Adoption: Trust as a Mediating Mechanism in an Extended TAM–TPB Framework - Hera Laxmi Devi Septiani; Irfan Nabhani; Nurul Qurrota A’ini (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid growth of financial technology has transformed access to financial services in Indonesia, promoting greater financial inclusion. However, concerns about trust, security, financial literacy, and ease of use continue to influence user adoption. This study investigates the effects of financial literacy, trust, and perceived ease of use on fintech adoption intention by integrating the Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). Objective: This research seeks to delineate the antecedents of fintech adoption intent in Indonesia by enriching the TAM–TPB architecture with financial literacy, trust, and perceived ease of use constructs, while probing the intermediary function of trust. Methods: Primary data were gathered from 315 Indonesian fintech users via a structured survey instrument. Results: The analysis revealed that financial literacy exerts favorable effects on trust, perceived ease of use, and adoption intention. Trust emerged as a consequential intermediary amplifying the pathway from financial literacy to usage intent. Additionally, PEOU was directly related to ITU without mediating the connection between FL and ITU. Trust was an important factor in ITU, specifically in developing markets where users had security concerns. The most effective method used by fintech providers to build trust was to offer open and safe platforms, as well as to enhance FL in increasing ITU. Conclusion: This work enriches the technology adoption scholarship by augmenting TAM and TPB with financial knowledge, provider confidence, and usability dimensions, offering actionable guidance for regulators and platform operators in emerging markets.